Inhibition of SerpinB9 to enhance granzyme B-based tumor therapy by using a modified biomimetic nanoplatform with a cascade strategy. (September 2022) - Han, Ran; Yu, Luting; Zhao, Chenxuan; Li, Ying; Ma, Yuying; Zhai, Yuewen; Qian, Zhiyu; Gu, Yueqing; Li, Siwen
Abstract: Granzyme B (GrB) is a pivotal killer factor in immunotherapy whose application is limited by hyposensitivity and unsatisfactory cellular uptake by tumor cells. In this study, it was proved that SerpinB9 (Sb9) downregulation can enhance the GrB susceptibility of tumor cells. Moreover, a nanocarrier fused with M1 macrophage exosomes (M1 Exo) and photothermal sensitive liposomes was constructed to efficiently transport GrB and siRNA of Sb9 to the cells. The nanocarrier is characterized by cascade tumor targeting acquired by photothermal effect-triggered increased expression of vascular cell adhesion molecule-1 (VCAM-1) in tumor tissue. Furthermore, the innate cytokines in M1 Exo are capable of regulating the tumor microenvironment by repolarizing M2 macrophages to the M1 type. Collectively, the multifunctional nanoplatform (S+G@ELP) enhances the lethality of GrB to tumor cells, activates a widespread immune response uniting with photothermal therapy (PTT), restrains the tumor progression and metastasis effectively, which is expected to provide new insights into GrB-based combinational tumor therapy.